A Half-Century of Possessive Individualism: C.B. Macpherson and the Twenty-First-Century Prospects of Liberalism - McKay, Ian (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2014)
C.B. Macpherson (1911–1987) was one of the most influential and controversial thinkers of his time, identified above all with the theses of “possessive individualism” and the “transfer of powers.” Although sometimes misidentified as a Marxist, and as such critiqued by proponents of the Cambridge School in the depths of the Cold War, Macpherson by his own description was attempting to use the resources of the Marxist tradition to clarify and revive liberalism. At a time when neo-liberalism has become hegemonic throughout western civil society, Macpherson is being revisited today. By treating property as a philosophical event, Macpherson transformed a commonsense of his time (and ours) into a politico-ethical problem, a proposition of great interest not only to historians but also to any emergent left seeking to define the outlines of a more rational future.